CONTROL REGION-mtDNA HETEROGENEITY OF KALIMANTAN FALSE GHARIAL (Tomistoma schlegelii) POPULATION: A PRELIMINARY STUDY - Hellen Kurniati (The East Java Biological Society, 2003)
The preliminary genetic study on Kalimantan